2019
DOI: 10.1111/echo.14486
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler‐derived atrial dyssynchrony predicts new‐onset atrial fibrillation during hospitalization for ST‐elevation myocardial infarction

Abstract: Background Atrial dyssynchrony, but not atrial enlargement/dysfunction, reflects acute atrial histopathological changes. It has been shown to be associated with new‐onset atrial fibrillation (NOAF) in various clinical conditions but was not studied in the acute phase of ST‐elevation myocardial infarction (STEMI) which is the aim of the current study. Methods A total of 440 STEMI patients underwent primary percutaneous coronary intervention (PCI) and were monitored for NOAF during hospitalization. Immediately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(65 reference statements)
2
3
0
Order By: Relevance
“…In the present study, hypertension was significantly higher in New-onset atrial fibrillation (77.2% vs. 48.3%, P value =0.012) and LDL significantly higher in New-onset atrial fibrillation (127.5 ± 10.2 vs. 121.6 ±10.263, P value=0.012). Our results are compatible with a study reported that the group with NOAF showed significantly higher prevalence of hypertension (P = .049) (8) . In the present study, conventional echocardiography data were insignificantly different between both groups except LAVI max which was significantly higher in New-onset atrial fibrillation (P value=0.024).…”
Section: A) B)supporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, hypertension was significantly higher in New-onset atrial fibrillation (77.2% vs. 48.3%, P value =0.012) and LDL significantly higher in New-onset atrial fibrillation (127.5 ± 10.2 vs. 121.6 ±10.263, P value=0.012). Our results are compatible with a study reported that the group with NOAF showed significantly higher prevalence of hypertension (P = .049) (8) . In the present study, conventional echocardiography data were insignificantly different between both groups except LAVI max which was significantly higher in New-onset atrial fibrillation (P value=0.024).…”
Section: A) B)supporting
confidence: 93%
“…In the present study, conventional echocardiography data were insignificantly different between both groups except LAVI max which was significantly higher in New-onset atrial fibrillation (P value=0.024). Our results agree with those documented by a study showed that indexed left atrial maximum volume (LAVI max ), left atrial dyssynchrony, and inter-atrial dyssynchrony were significantly higher in NOAF group (P < 0.001) (8). In contrast to this observation, other studies failed to demonstrate any predictive value of LAVI max in the acute phase after STEMI (9,10) .…”
Section: A) B)supporting
confidence: 92%
See 1 more Smart Citation
“…We selected the median value of LIAEMD for comparison. This selection was supported by evidence provided by previous investigations, according to which the mean of LIAEMD in control subjects ranges between 17 ms and 23 ms The case groups of these studies were comprised of patients with induced AF in invasive electrophysiology study, patients with paroxysmal AF, hypertensive patients with paroxysmal AF, and patients with acute myocardial infarction complicated with new‐onset AF . It is also worthy of note that LIAEMD was significantly statistically different between the control and case groups of these studies.…”
Section: Discussionmentioning
confidence: 58%
“…Determining predictors of NOAF has been an important focus of research. Previous studies have proposed older age, 20 and comorbidities, 4 such as hypertension, 21 diabetes mellitus, 19 culprit lesion site, 13 CKD, 5 and neutrophil/lymphocyte ratio. 22 Rene et al 18 reported age, and BMI as independent predictors for the development of AF following MI.…”
Section: Discussionmentioning
confidence: 99%